Assessment and Management of HIV Distal Sensory Peripheral Neuropathy: Understanding the Symptoms - Anastasi, Joyce K. (J Nurse Pract, 2020)
Distal sensory peripheral neuropathy (HIV-DSP) affects upwards of 50% of people living with HIV. Causing often debilitating symptoms of tingling, numbness and burning, HIV-DSP can result in disability, unemployment and low quality of life. Comorbidities further complicate nursing care, heightening risk of polypharmacy and symptom exacerbation. Therefore, a neurological sensory assessment, combined with the patient’s self-report of symptoms, can help nurse practitioners visualize, quantify and understand symptoms. Common pharmacological interventions include antiepileptics, antidepressants, analgesics and medical marijuana. The complexity of care for individuals with HIV-DSP merits a comprehensive approach. Implications for practice include interdisciplinary management with neurologists, podiatrists, mental health providers, and nurse-led counseling inclusive of patient safety teaching.